Penerapan Smart Economy pada UMKM Ladang Jamur Tiram Indonesia di Dolok Masihul, Serdang Bedagai - Sinaga, Teguh Trifena; Sihombing, Marlon; Irmayani, Tengku (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
This study aims to analyze the application of the smart economy concept in MSMEs of the Indonesian Oyster Mushroom Farm (Jatiramdo) located in Block 10 Village, Dolok Masihul District, Serdang Bedagai Regency. Through a qualitative approach with a case study method, this study explores the forms of technology adoption, digitalization challenges, and village institutional support in the digital transformation process of rural MSMEs. The results of the study show that Jatiramdo has carried out a gradual digital transformation through the use of social media for marketing, the use of semi-modern production tools, and application-based financial recording. However, a number of challenges such as low digital literacy, limited internet infrastructure, and suboptimal institutional support hinder the expansion of technology adoption. The role of the village government as a facilitator is quite significant, although it has not been followed by sustainable strategic policies. Overall, the implementation of the smart economy in Jatiramdo not only increases income and business competitiveness, but also strengthens the social and institutional structure of the village. These findings indicate that a community-based digitalization model can be an important pillar in inclusive and sustainable village economic development.